Efficacy of systemic adoptive transfer immunotherapy targeting NY-ESO-1 for glioblastoma - Everson, Richard G. (Neuro Oncol, 2016)
BACKGROUND: Immunotherapy is an ideal treatment modality to specifically target the diffusely infiltrative tumor cells of malignant gliomas while sparing the normal brain parenchyma. However, progress in the development of these therapies for glioblastoma has been slow due to the lack of immunogenic antigen targets that are expressed uniformly and selectively by gliomas. METHODS: We utilized human glioblastoma cell cultures to induce expression of New York–esophageal squamous cell carcinoma (NY-ESO-1) following in vitro treatment with the demethylating agent decitabine. We then investigated the phenotype of lymphocytes specific for NY-ESO-1 using flow cytometry analysis and cytotoxicity against cells treated with decitabine using the xCelligence real-time cytotoxicity assay. Finally, we examined the in vivo application of this immune therapy using an intracranially implanted xenograft model for in situ T cell trafficking, survival, and tissue studies. RESULTS: Our studies showed that treatment of intracranial glioma–bearing mice with decitabine reliably and consistently induced the expression of an immunogenic tumor-rejection antigen, NY-ESO-1, specifically in glioma cells and not in normal brain tissue. The upregulation of NY-ESO-1 by intracranial gliomas was associated with the migration of adoptively transferred NY-ESO-1–specific lymphocytes along white matter tracts to these tumors in the brain. Similarly, NY-ESO-1–specific adoptive T cell therapy demonstrated antitumor activity after decitabine treatment and conferred a highly significant survival benefit to mice bearing established intracranial human glioma xenografts. Transfer of NY-ESO-1–specific T cells systemically was superior to intracranial administration and resulted in significantly extended and long-term survival of animals. CONCLUSION: These results reveal an innovative, clinically feasible strategy for the treatment of glioblastoma.